Cellular and molecular mechanisms of action of ovarian steroid hormones II: Regulation of sexual behavior in female rodents - Pfaus, James G; García-Juárez, Marcos; Ordóñez, Raymundo Domínguez; Tecamachaltzi-Silvarán, Miriam B; Lucio, Rosa Angélica; González-Flores, Oscar (Neuroscience and biobehavioral reviews, 2025)
Female sexual behaviors in rodents (lordosis and appetitive or "proceptive" behaviors) are induced through a genomic mechanism by the sequential actions of estradiol (E2) and progesterone (P), or E2 and testosterone (T) at their respective receptors. However, non-steroidal agents, such as gonadotropin-releasing hormone (GnRH), Prostaglandin E2 (PGE2), noradrenaline, dopamine, oxytocin, α-melanocyte stimulating hormone, nitric oxide, leptin, apelin, and others, facilitate different aspects of female sexual behavior through their cellular and intracellular effects at the membrane and genomic levels in ovariectomized rats primed with E2. These neurotransmitters often act as intermediaries of E2 and P (or T). The classical model of steroid hormone action through intracellular receptor binding has been complemented by an alternative scenario wherein the steroid functions as a transcription factor after binding the receptor protein to DNA. Another possible mechanism occurs through the activation of second messenger systems (cyclic AMP, cyclic GMP, calcium), which subsequently initiate phosphorylation events via diverse kinase systems (protein kinases A, G, or C). These kinases target the progesterone receptor (PR) or associated effector proteins that connect the PR to the trans-activation machinery. This may also happen to the androgen receptor (AR). In addition, other cellular mechanisms could be involved since the chemical structure of these non-steroidal agents causes a change in their lipophobicity that prevents them from penetrating the cell and exerting direct transcriptional effects; however, they can exert effects on different components of the cell membrane activating a cross-talk between the cell membrane and the regulation of the transcriptional mechanisms.
Keywords: Rodentia; Sexual Behavior, Animal; Cellular mechanism; Female; Female sexual behavior; Steroid action; Progesterone receptor; Progesterone; pohlavní steroidní hormony; zvířata; Second messengers; ženské pohlaví; Gonadal Steroid Hormones; Estrogen receptor; hlodavci; progesteron; Androgen receptor; Animals; sexuální chování zvířat